Audit Opinion and Audit Characteristic: Study of Voluntary Auditor Switching - Dewi, Ni Putu Shinta; Febriyanti, Ni Luh Putu Tara Verjinia; Rustiarini, Ni Wayan (EQUITY, 2021)
Auditor switching is a change of public accountant (or accounting firm) in a company. The voluntary auditor switching is carried out according to the client’s request to change his auditor, and no regulations require him to switch auditors. This study analyzes the factors influencing voluntary auditor switching in manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. This research population is all manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The research sample was selected using a purposive sampling method. The sample amounted to 98 manufacturing companies, and the total sample was 294 company units. The analytical tool used to test the hypothesis is logistic regression analysis. The results showed that audit fees and audit tenure had a positive effect on auditor switching. Audit opinion, going concern opinion, and audit reporting lag do not affect auditor switching.